2021
DOI: 10.1002/cssc.202101991
|View full text |Cite
|
Sign up to set email alerts
|

Multisize CoS2 Particles Intercalated/Coated‐Montmorillonite as Efficient Sulfur Host for High‐Performance Lithium‐Sulfur Batteries

Abstract: The chemisorption and catalysis of lithium polysulfides (LiPSs) are effective strategies to suppress the shuttle effect in lithiumsulfur (LiÀ S) batteries. Herein, multisize CoS 2 particles intercalated/coated-montmorillonite (MMT) as an efficient sulfur host is synthesized. As expected, the obtained S/CoS 2 @MMT cathode achieves an absorption-catalysis synergistic effect through the polar MMT aluminosilicate sheets and the well-dispersed nanomicron CoS 2 particles. Furthermore, efficient interlamellar ion pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 49 publications
(135 reference statements)
1
22
0
Order By: Relevance
“…The CoS 2 @montmorillonite composite was synthesized according to our previous work. 34 Firstly, a general cation exchange process was performed to replace the interlaminar cations (i.e., Mg 2+ , Ca 2+ , Na + ) of montmorillonite by Co 2+ . Subsequently, a facile hydrothermal method was adopted for the grain growth of CoS 2 , during which the CoS 2 particles were simultaneously synthesized on the surfaces and in the interlayers of montmorillonite.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The CoS 2 @montmorillonite composite was synthesized according to our previous work. 34 Firstly, a general cation exchange process was performed to replace the interlaminar cations (i.e., Mg 2+ , Ca 2+ , Na + ) of montmorillonite by Co 2+ . Subsequently, a facile hydrothermal method was adopted for the grain growth of CoS 2 , during which the CoS 2 particles were simultaneously synthesized on the surfaces and in the interlayers of montmorillonite.…”
Section: Resultsmentioning
confidence: 99%
“…The morphology and structure of the CoS 2 @montmorillonite composite have been thoroughly studied in our previous work and it was reported that the montmorillonite matrix possesses a 2D layered structure with a large basal spacing of 1.94 nm, and the CoS 2 microcrystals ( particle size ∼200 nm) and ultrafine nanoparticles ( particle size ∼5 nm) are embedded and distributed uniformly on the surface and in the interlayers of the montmorillonite matrix, respectively. 34 transformation (FFT) images (Fig. S2b and d †) reveal that the lattice distances of the CoS 2 microcrystals and nanoparticles are 0.320 and 0.226 nm based on calculations, which are indexed to the (111) and (211) planes of CoS 2 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations